Gundelia dersim and Gundelia munzuriensis (Compositae), two new species from Turkey - Vitek, Ernst; Yüce, Ebru; Ergin, Cemil (Phytotaxa, 2014)
Two new species of Gundelia (Compositae) are described from Turkey, G. dersim Vitek, Yüce & Ergin sp. nov. and G. munzuriensis Vitek, Yüce & Ergin sp. nov.